An environmental perturbation at AD 600 and subsequent human impacts recorded by multi-proxy records from the sediments of Lake Mayinghai, North China. (December 2018) - Shen, Zhongwei; Liu, Jianbao; Xie, Chengling; Zhang, Xiaosen; Chen, Fahu
Modern observations indicate that a dramatic increase in the intensity of human activity is the main cause of environmental degradation. However, the timing of the onset of significant human impacts on regional environments during the historical period is unclear. In this study, an AMS 14 C-dated 878-cm-long sediment core (MYH14B), from Lake Mayinghai in the farming-pastoral ecotone of northern China, was used to study the long-term relationship between the ecological environment and human activity. The area is characterized by a fragile ecological system and is sensitive to environmental change and human activity. We found evidence for abrupt sedimentary changes beginning around AD 600, revealed by the increased (decreased) content of exogenous (endogenous) elements, a decrease in grain size and the appearance of quartz particles with V-shaped percussion cracks. This evidence indicates an abrupt increase in sediments transported by surface run-off and that a large amount of freshwater was injected into the lake. The climate was stable at the time and therefore, combined with historical documentary evidence, we attribute this event to the excavation of a river channel flowing into the lake, in association with the construction of nearby Fenyang Palace by Emperor Yang during the Sui Dynasty. Subsequently, the content of exogenous elements in the sediments was significantly positively correlated with the intensity of deforestation, cultivation and grazing, indicating that these elements can be used as a proxy of the intensity of human activity. The variation of this proxy demonstrates that intensified human activity occurred during AD 600– 1100 and after AD 1350, and that human activity weakened during AD 1100–1350, which is supported by evidence from historical accounts and changes in the population size of Shanxi Province. Overall, our findings reveal a substantial conflict between human activity and environmental stability in the farming-pastoral ecotone of northern China during the Sui Dynasty (AD 600). In addition, the sensitivity of the lake response to human activity revealed in this study highlights the importance of further paleolimnological studies in the region.